2012
DOI: 10.1002/jclp.21859
|View full text |Cite
|
Sign up to set email alerts
|

A Cultural and Social Cognitive Model of Differences in Acculturation Orientations, Alcohol Expectancies, and Alcohol‐Related Risk Behaviors Among Hispanic College Students

Abstract: Our findings provided relevant data that are informative for preventing alcohol and related risk behaviors among Hispanic college students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 74 publications
3
52
0
Order By: Relevance
“…However, results from a study by Venegas, Cooper, Naylor, Hanson, and Blow (2012) found no differences in levels of biculturalism between heavyepisodic drinkers and nonheavy episodic drinkers. Given that multiple types of biculturalism likely exist, the use of latent class modeling (e.g., Des Rosiers et al, 2013) in acculturation research will greatly enhance our understanding of what it means to be bicultural as well as its protective role against alcohol use and misuse. 6.…”
Section: Implications For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…However, results from a study by Venegas, Cooper, Naylor, Hanson, and Blow (2012) found no differences in levels of biculturalism between heavyepisodic drinkers and nonheavy episodic drinkers. Given that multiple types of biculturalism likely exist, the use of latent class modeling (e.g., Des Rosiers et al, 2013) in acculturation research will greatly enhance our understanding of what it means to be bicultural as well as its protective role against alcohol use and misuse. 6.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Finally, Des Rosiers, Schwartz, Zamboanga, Ham, and Huang (2013) utilized a bidimensional approach and latent class modeling to classify Hispanic college students into acculturation orientation categories. They empirically derived five acculturation orientations:…”
Section: How Is Acculturation Related To Alcohol Use?mentioning
confidence: 99%
“…Conversely, higher enculturation is associated with less alcohol consumption (Des Rosiers, Schwartz, Zamboanga, Ham, & Huang, 2013) and fewer depressive symptoms (Cano & Castillo, 2010). However, the extant research on enculturation is limited (Castillo & Caver, 2009) and is heavily focused on the behavioral domain of ethnocultural orientation (Abraído-Lanza et al, 2006).…”
Section: Enthnocultural Orientation and Healthmentioning
confidence: 99%
“…Among Hispanic college students, acculturation has often been identified as a cultural correlate of drinking behaviors (9)(10)(11)(12)(13)(14)(15)(16)(17). Acculturation is the process of psychological, social, and cultural change and adaptation that takes place when cultural minorities engage in extended close interactions with the majority culture (18).…”
Section: Acculturationmentioning
confidence: 99%
“…Only a handful of alcohol use studies with Hispanic college students have utilized bidimensional conceptions of acculturation, and these results have also yielded mixed findings. For example, Des Rosiers et al (11) used latent class modeling to create five acculturative orientations based on Berry's (24) classic typology: assimilated (acquires US practices and discards one's cultural heritage), separated (rejects US practices and retains one's cultural heritage), and three bicultural groups that involve both adopting US practices and retaining those from one's cultural heritage -separated bicultural, high bicultural, and low bicultural. Des Rosiers et al (11) found that students who were in the three bicultural groups reported lower levels of drinking-related risk behaviors than students in the assimilated group.…”
Section: Acculturation and Alcohol Use Among Hispanic College Studentsmentioning
confidence: 99%